Komunikasi Politik Anggota Legislatif Perempuan di DPRD Provinsi Gorontalo - Buusungi, Faini; Katili, Andi Yusuf (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2024)
This research aims to find out how political communication is between female legislative members in the Gorontalo Province DPRD and their involvement in politics as legislative members. This research is descriptive research with data collection techniques, namely, observation, interviews and documentation. The research results found that there were 28.8% female legislative members, almost in accordance with the provisions of the election law, a step forward compared to the previous number. Women legislative members in Gorontalo Province, get an added value because they can fight for one of the fields that was previously from Bureau to Service, so that their struggle in the courtroom is not just a figment, but has resulted in a struggle that is recognized by the majority of men, so that women's rights have been accommodated in decisions and agreements fought for by female legislative members in the Gorontalo Province DPRD. The conclusion that can be drawn from the research results is that female legislative members in the Gorontalo Province DPRD received support from the majority, and provided an increase in the number of seats previously available, so that the struggle for women's rights received better attention, from the Women's Empowerment Bureau to the Department Women's Empowerment, evidence of clarity in the work of female legislative members so far has begun to gradually progress towards maximum results, for the benefit of society.